Probing Enantiospecific Interactions between Proline and an L-Glutathione Self-Assembled Monolayer by Modulation Excitation ATR-IR Spectroscopy - Bieri, Marco; Bürgi, Thomas (My University, 2005)
The interaction of proline with self-assembled monolayers (SAMs) of L-Glutathione (γ-glu-cys-gly) on gold was investigated by a combination of attenuated total reflection (ATR-IR) infrared and modulation excitation spectroscopy (MES). The latter technique makes use of phase-sensitive detection of periodically varying signals and allows discrimination between species with different kinetics such as dissolved proline and adsorbed molecules. By applying a convection−diffusion model coupled to adsorption and desorption, it was possible to extract relative adsorption and desorption rates from the experimental data for the two enantiomers of proline, fully accounting for mass transport within the flow-through cell. The results show that, in particular, the desorption kinetics is different for the two enantiomers. Therefore, the L-Glutathione SAM can discriminate between enantiomers, d-proline being stronger bound. The IR spectra reveal that upon interaction with proline the adsorbed L-Glutathione is protonated at the gly part of the molecule, which, in the absence of proline, is bound to the gold surface as carboxylate. The observed protonation of adsorbed L-Glutathione upon interaction with proline goes along with a structural change of the former, which seems to play an important role for enantiodiscrimination.